Magnetic Co3O4/reduced graphene oxide nanocomposite as a superior heterogeneous catalyst for one-pot oxidative esterification of aldehydes to methyl esters. Issue 108 (19th October 2015) - Panwar, Vineeta; Al-Nafiey, Amer; Addad, Ahmed; Sieber, Brigitte; Roussel, Pascal; Boukherroub, Rabah; Jain, Suman L.
Abstract : Magnetic Co3 O4 /reduced graphene oxide nanocomposite as a superior heterogeneous catalyst for one-pot oxidative esterification of aldehydes to methyl esters. Abstract : A magnetically separable hybrid material consisting of Co3 O4 nanoparticles supported on reduced graphene oxide (Co3 O4 /rGO) was synthesized through a simple co-reduction process of graphene oxide (GO) and cobalt chloride (CoCl2 ) using sodium borohydride (NaBH4 ). The Co3 O4 /rGO heterogeneous catalyst exhibited a high-performance for the oxidative esterification of aldehydes to the corresponding methyl esters using tert -butyl hydroperoxide (TBHP) as an oxidant. Owing to the synergistic effect of rGO support, the hybrid catalyst exhibited superior catalytic activity to the corresponding cobalt oxide catalyst. Importantly, the synthesized hybrid possesses good magnetic properties, which enable facile recovery of the catalyst by using an external magnet.